Proses Pengambilan Keputusan untuk Memakai Cadar pada Muslimah - Author: Fitriani; Yulianti Dwi Astuti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
This study aims to find out and understanding the decision making process on moslem women wearing the face veil (niqaab) and the factors influences moslem women wearing the face veil. The theory used in this study based on the decision making process theory which proposed by Gitosudarmo and Sudita (1997). Total respondents in this study are two moslem women in the aged of 20 to 25 years old, unmarried, wearing the face veil for at least one year, and the first time using the face veil is when still registered as an active student at a particular university in Yogyakarta. The data collection methods used in this study were interviews using an interview guide during the interview process. This study found that the two respondents had been going through the decision making process that similar to the theory propounded by Gitosudarmo and Sudita (1997) which includes setting the goals, identifying problems, developing various solutions alternative, evaluation on various solutions alternative that have been developed and choose an alternative that has been evaluated, implementing the decisions, evaluation upon the implemented decision, monitoring and perform corrective action. Despite all two respondents had known the consequences (risk) that will be encountered, both respondents continue to implement the decision because of the higher achievement or expectations, i.e. preserve their modesty, minimizing the possibility of individuals to cause other people immoral behavior, wanted to became a better person, expect Allah's blessings and to be put in paradise with variety of pleasures in it and so on. Sometimes, the decision was also implemented to avoid something worse that might happen later in the future which is severe consequences (risk) in the hereafter (aakhirah).Keywords: decision making process, face veil (niqaab)